Information Asymmetry Effect on Stock Liquidity Effect on Dividend Payout in Market Microstructure in Indonesia - Singh, Sanju Kumar; Christiana, Nova; Upadhyay, Jitendra Prasad; Niroula, Ballav; Sitanggang, Eva Rianty Angelina (Airlangga Journal of Innovation Management, 2024)
The impact of market microstructure in shaping corporate governance has been distinguished in several previous research. Market Microstructure becomes prominent factor in emerging markets. This study tested the effect of market microstructure, in the scheme of stock liquidity, on dividend payouts. This study has set focus mainly on the impact of stock liquidity on the corporate payout policy. Later, the researcher examined the interaction given to the stock liquidity factor with information transparency and agency problem properties since the researcher believed that transparency is linked to the and, subsequently, affecting the corporate agents. This research examined observations using quantitative research method, Tobit regression on 256 non-financial firms of the Indonesian capital market during 2010-2018. Stock liquidity significantly impacted dividend policy. The result showed robustness with other stock liquidity measures. This study found that information asymmetry and agency problems had a moderation effect on stock liquidity effect on dividend payout. However, the interaction of stock liquidity and disparity of control rights and cash flow rights did not give a moderation effect on the dividend payout policy. The result supports the notion that dividend payout is an outcome of firm good governance and an inverse of dividend signaling theory.